What causes the child penalty? Evidence from same sex couples and policy reforms - Martin Eckhoff Andresen; Emily Nix (Statistics Norway, Research Department, 2019)
Women experience significant reductions in labor market income following the birth of children, while their male partners experience no such income drops. This "relative child penalty" has been well documented and accounts for a significant amount of the gender income gap. In this paper we do two things. First, we use a simple household model to better understand the potential mechanisms driving the child penalty, which include gender norms around child care, female preferences for child care, efficient specialization within households, and the biological cost of giving birth. The model, combined with the estimated child penalties for heterosexual and same sex couples, suggests that the child penalty experienced by women in heterosexual couples is primarily explained by female preferences for child care and gender norms, with a smaller contribution due to the biological costs of giving birth. Second, we provide causal estimates on the impact of two family policies aimed at reducing the relative child penalty: paternity leave and subsidized early child care. Our precise and robust regression discontinuity results show no significant impact of paternity leave use on the relative child penalty. Early subsidized care seems to have more promise as a policy tool for affecting child penalties, as we find a 25% reduction in child penalties per year of child care use from a large Norwegian reform that expanded access to child care.
Keywords: I21; J13; J22; J71; 330; Gender wage gap; labor supply; child penalty; paternity leave; child care; same sexcouples; event study; regression discontinuity; instrumental variables